Fulfilling Iraq's Potential - Kim, Jim Yong (World Bank, Washington, DC, 2019)
Jim Yong Kim, President of the World Bank Group, noted that even in the face of substantial challenges, democracy is taking root in Iraq. He believes that Iraq’s success can bring stability and prosperity to hundreds of millions of people. He discussed three critical steps that Iraq must continue to build the foundations of an inclusive society. First, look beyond the traditional social, cultural, and geographic boundaries in Iraq. Empower all its regions, and give more capacity to local government, all the way to the municipal level. Second, Iraq needs to diversify its economy. Third, Iraq needs to put its economic house in order, reducing waste of precious resources, strengthening accountability, and undertaking important, necessary reforms. In the energy sector, for example, reforms must address subsidies which contribute to chronic and pervasive shortages of electricity. He concluded by saying that through war, violence and strife, the Iraqi people have shown the world the meaning of resistance, resilience, courage, and nobility.